(untitled) (Scientific journal of the Fergana State University, 2023)
In this article, the issue of the importance of using new pedagogical methods, collaborative teaching technology and working in small groups aimed at preparing future chemistry teachers to implement environmental education in chemistry teaching is analyzed. According to him, the article discusses the importance of using collaborative teaching in order to improve the methodological preparation of future chemistry teachers in teaching chemistry.